Therapeutic communication of nursing and organ donation - Amancio Castro, Ana María (2021)
Throughout civilization organ donation is an altruistic gesture taking into account as the major act of kindness between human beings and therapeutic communication is a useful tool to contribute in this process. The objective tried to determine the relations hip between therapeutic communication of registered nurses and organ donation. Materials and Methods: This study has a quantitative approach; information was collected using a questionnaire that was applied to 119 registered nurses. Results: denotative results 50.4% and communicative goals 54,62% are conclusive that it exists a good level of communication from regular to good. Discussion: Results comparable with a study made by Romero, Y., who found that it exists an attitude of negative direction that would contribute to decrease probability of donation, harmful to people requiring transplant, intensity is adverse. Verifying concordances with obtained data in this research because they denote medium level in both variables with direct and positive relationship. Conclusions: It was observed a direct and positive relationship between therapeutic communication and organ donation.